A study on the “buy now” service of Bikroy.com and the causes of its success - Rinkue, Mir Istiak Ahmed (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2016.